Proceedings of the 8th ACM on Multimedia Systems Conference 2017
DOI: 10.1145/3083187.3083189
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Multimedia System for Gastrointestinal Tract Disease Detection

Abstract: Analysis of medical videos for detection of abnormalities and diseases requires both high precision and recall, but also real-time processing for live feedback and scalability for massive screening of entire populations. Existing work on this field does not provide the necessary combination of retrieval accuracy and performance. In this paper, a multimedia system is presented where the aim is to tackle automatic analysis of videos from the human gastrointestinal (GI) tract. The system includes the whole pipeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 50 publications
0
103
1
Order By: Relevance
“…For the FDSI sub-task, we have also opted for a CNN and a transfer learning-based classification approach, previously validated in a different application domain in our work [41]. In fact, we initially tried to apply the well-performing GAN approach introduced in our previous works for the flood detection satellite imagery [2] and medical imagery [42,43].…”
Section: Methodology For Fdsi Taskmentioning
confidence: 99%
“…For the FDSI sub-task, we have also opted for a CNN and a transfer learning-based classification approach, previously validated in a different application domain in our work [41]. In fact, we initially tried to apply the well-performing GAN approach introduced in our previous works for the flood detection satellite imagery [2] and medical imagery [42,43].…”
Section: Methodology For Fdsi Taskmentioning
confidence: 99%
“…As a natural step forward, we designed and implemented deep-learning-based [117] and deep-featurebased [87] single-and multi-class classifiers for the detection subsystem, and evaluated and compared them with global-feature-based classifiers [99]. We demonstrated that our detection system can reach a detection performance comparable with state-of-the-art polyp detection approaches, while providing higher processing speeds and reaching our real-time goals [91,119].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they can also tear intestinal walls in case of severe medical conditions, and endoscopies such as enteroscopy and push enteroscopy are uncomfortable for the patients. They are performed in real-time and are challenging to scale to a larger population [91]. Also, the procedure is expensive.…”
Section: Gastrointestinal Tract Case Studymentioning
confidence: 99%
“…A machine learning approach that has been reborn and lately gained a lot of interest is neural networks [14] which is a type of machine learning which loosely mimics how a biological brain learns, i.e., being able to learn general concepts from concrete examples. Neural networks are also used in the medical domain, e.g., for micro-calcification detection in mammogram images [15], detecting breast cancer [3], colonic polyp detection [5], [6], [7], [8], [9] and lung cancer [4]. To perform the analysis of the data, deep neural networks (deep learning) contain multiple network layers where each layer can learn different abstraction levels of the data using the input of previous layers.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Thus, detection and removal of polyps therefore prevents the development of cancer, and our detection challenge is shown in figure 1, where the polyps must be detected and identified among images and video frames also containing normal mucosa and various other anatomical landmarks and abnormalities. With respect to using neural networks for this type of abnormality detection, research have already proven that neural networks can be suitable, e.g., for similar problems detecting breast cancer [3], lung cancer [4], and for polyp detection in particular [5], [6], [7], [8], [9]. In this paper, we enhance our neural network-based EIR system (named after a Norse goddess associated with medical skills) with data enhancement methods and assess their effect on detection performance.…”
Section: Introductionmentioning
confidence: 99%